The Domestication of Wildness in the Social Medias Universe: Raccoons and Foxes as Pets - Terracciano, Bianca (E|C, 2020)
This contribution deals with the incidence of foxes and raccoons in the intermedial semiosphere as unconventional puppies, or rather pet. Their representation in myths, in fictional worlds, is certainly less frequent than that of other animals, but precisely for this reason it is a good example of an effective discourse of the dominant isotopias on a thematic and figurative level, since it is more dense and circumscribed. The pet status of foxes and raccoons can be found in the dedicated profiles that dot the social networks, where peculiar contents are shared, even attributable to the sphere of ethology, in which invariant trans-species have been found. The digital conversations triggered by them open interesting perspectives on the dichotomy between wild and domestic, also with regard to Italian and international legislative frameworks.